FSMP-12. A ROLE FOR PROLINE BIOSYNTHESIS IN HYPOXIC GLIOBLASTOMA. (25th March 2021) - Vettore, Lisa; Westbrook, Rebecca; Roberts, Jennie; Escribano-Gonzalez, Cristina; Cuozzo, Federica; Hodson, David; Watts, Colin; Nixon, Colin; Tennant, Daniel
Abstract: Hypoxia is a common feature of glioblastoma, and a known driver of therapy resistance in brain tumours. Understanding the metabolic adaptations to hypoxia is key to develop new effective treatments for patients. A recent screening study highlighted Pyrroline-5-carboxylate reductase-like (PYCRL) as one of the top three genes that allowed tumour survival in hypoxia. PYCRL is one of the three enzymes involved in proline biosynthesis along with the mitochondrial pyrroline-5-carboxylate reductase 1 and 2 (PYCR1/2). The latter use glutamine as the carbon source to fuel the pyrroline-5-carboxylate (P5C)-to-proline reaction, whereas the cytosolic PYCRL is known to use ornithine to produce proline. Our investigations have shown that PYCRL differs from PYCR1 and 2 in the impact on cellular redox, which is a critical factor in hypoxic survival. Our data suggest that PYCRL activity is required for normal regulation of glioblastoma cell growth and the ability to deal with cellular stress, and that this enzyme may therefore represent a novel target in the treatment of these devastating tumours. Importantly, our study also begins to provide much-needed clarity over the network surrounding proline metabolism and redox maintenance.